2020
DOI: 10.1111/srt.12976
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of swine and human skin: Correlations between Raman spectroscopy, Tensile testing, Atomic force microscopy (AFM), Scanning electron microscopy (SEM), and Multiphoton microscopy (MPM)

Abstract: Background: Swine dorsum is commonly utilized as a model for studying skin wounds and assessment of dermatological and cosmetic medicaments. The human abdomen is a common location for dermatological intervention.Objective: This study provides a correlation between spectral, mechanical, and structural characterization techniques, utilized for evaluating human abdominal skin and swine dorsum. Methods: Raman spectroscopy (RS), tensile testing, ballistometry, AFM, SEM, and MPM were utilized to characterize and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…elastic modulus) by a smooth transition and to provide stress relief at the interface between dissimilar materials (i.e., lipid polyester and cell wall polysaccharides) (Liu et al ., 2017). Such structural gradients result in an increased toughness and have been observed in many biological materials such as the dentin-enamel junction in mammalian teeth (Naleway et al ., 2015), the tendon-ligament (Lu & Thomopoulos, 2013), collagen/elastin of skin (Labroo et al ., 2021) and chitin/protein in squid beaks (Miserez et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…elastic modulus) by a smooth transition and to provide stress relief at the interface between dissimilar materials (i.e., lipid polyester and cell wall polysaccharides) (Liu et al ., 2017). Such structural gradients result in an increased toughness and have been observed in many biological materials such as the dentin-enamel junction in mammalian teeth (Naleway et al ., 2015), the tendon-ligament (Lu & Thomopoulos, 2013), collagen/elastin of skin (Labroo et al ., 2021) and chitin/protein in squid beaks (Miserez et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A formalin preserved rat skin of control, standard group, and formulation group was cut into 7 cm × 3 cm slices to be analyzed by UTM at Centralized Research Lab at the University of Peshawar. The thickness of the skin was 2.5 mm and a force (KN) of 1 KN till peak load reached to its maximum at speed of 1 mm/minute was applied (Brosh et al., 2004 ; Labroo et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, sodium alginate prevents some interactions between collagen fibers resulting in a hydrogel which does not sustain elongation. We compared Col/SA hydrogel, sodium alginate/methylcellulose hydrogel GelMA/sodium alginate hydrogel and human skin tissue [61][62][63]. We found that the mechanical properties of Col/SA hydrogels are at a higher level among current hydrogels, but they are significantly inferior to the mechanical properties of human skin.…”
Section: Mechanical Properties Of Hydrogelmentioning
confidence: 96%